Role of institutions for effective telecommunications regulation: Palestine as a case study - Omar Dhaher (International Telecommunications Society (ITS), 2011)
This paper investigates Palestine's institutional foundations in order to decide on the most appropriate telecommunications regulatory system. It is based on the work of Levy and Spiller's institutional endowment framework. Comments and adjustments to the framework are also discussed and regulation within fragile states is also analyzed. Depending on international reports and interviews with key stakeholders of the telecommunications sector, the paper present Palestine's institutional endowment framework in addition to adjustments needed to accommodate fragility and occupation.
Keywords: L96; Z00; 330; Telecommunications regulation; Regulatory design; Institutional Reform